Implementasi Blooket sebagai Media Pembelajaran Interaktif untuk Meningkatkan Partisipasi Peserta Didik - Mega Agustini; Eriawaty Eriawaty; Sri Rohaetin (FKIP, Universitas Palangka Raya, 2026)
This study aims to analyze the use of digital interactive learning media, particularly Blooket, in improving students’ motivation, participation, and learning experiences in the Economics Education Study Program at Universitas Palangka Raya. The research employed a qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The learning process was conducted directly in the classroom using Blooket as an interactive learning medium. The results showed that the use of interactive learning media was able to create a more active, enjoyable, and communicative learning atmosphere. Students appeared more enthusiastic, focused, and actively involved during the learning process. In addition, the use of Blooket increased students’ confidence and learning motivation through game elements and healthy competition. However, several challenges were also identified, including differences in students’ understanding abilities, the need for more effective time management, and the necessity for deeper material explanations. Overall, the use of digital interactive learning media proved effective in supporting the improvement of learning quality in the digital era.